THE ROLE OF BLOCKCHAIN IN ZAKAT MANAGEMENT - Yuannisa, Rizka Adlia; Nasution, Yenni Samri Juliati (Al-Muhtarifin: Islamic Banking and Islamic Economic Journal, 2024)
The global financial system continues to experience rapid development along with advances in information technology. The development of information technology can create opportunities and even challenges at the same timeBlockchain in the field of Islamic economics, adaptation to digital systems is also a major concern, however the Islamic economic system must be able to adapt to increasingly rapid technology. This research uses qualitative methods with library research. The results of this research: The application of Sharia smart contracts in blockchain has the potential to provide various benefits, such as facilitating fair and transparent transactions, minimizing the risk of violating sharia principles, and increasing public trust in carrying out digital transactions. Having a blockchain system in managing zakat is very important, because in the blockchain zakat system there is already some data from mustahik and programs from zakat institutions that have been provided and verified by the zakat institution itself. Then in this blockchain zakat system, the muzakki process who will pay zakat can distribute their zakat directly through programs or mustahik whose data is already in the system. Furthermore, the transaction process will be verified by a verifier who has been determined by the zakat institution regarding the truth of the transaction carried out by the mustahik.Keyword: Blockchain, Digital Economy, Islamic Economy, Zakat